High Platform Elevations Highlight the Role of Storms and Spring Tides in Salt Marsh Evolution - Goodwin, Guillaume C. H.; Mudd, Simon M. (Frontiers in Environmental Science, 2019)
We combine sea level records and repeat lidar surveys at 8 sites in the United Kingdom and the United States to explore controls on marsh accretion. We compare marsh elevations relative to sea level as well as lidar-derived marsh accretion rates to simple 0-dimensional settling simulations in order to explore constraints on suspended sediment concentration and particle size. We find that the marsh platforms examined occupy a narrow range of elevations in the upper tidal frame, situated between Mean High Tide MHT and the Observed Highest High Tide OHHT. Under sinusoidal tidal forcing, common in marsh accretion models, marshes at these elevations are never inundated, highlighting the inadequacy of sinusoidal forcing in numerical models of salt marshes. Forcing the model with year-long tidal records, deposition rates follow hyperbolic contour lines when expressed as a function of sediment concentration and median grain size. We also observe that when using a median sediment grain size D50 = 50 μm and sediment concentrations derived from satellite data, modeled deposition rates are much lower than when using field data. We find that the deposition of coarse, concentrated sediment is necessary for platforms in the upper tidal frame to withstand sea level rise, suggesting a strong dependance on infrequent high-deposition events. This is particularly true for marshes that are very high in the tidal frame, making accretion increasingly storm-driven as marsh platforms gain elevation. Finally, we reflect on the capacity of marshes to regenerate after erosion events within a context of changing sediment supply conditions.